2023
DOI: 10.5194/cp-19-803-2023
|View full text |Cite
|
Sign up to set email alerts
|

Holocene climates of the Iberian Peninsula: pollen-based reconstructions of changes in the west–east gradient of temperature and moisture

Abstract: Abstract. The Iberian Peninsula is characterized by a steep west–east moisture gradient at present, reflecting the dominance of maritime influences along the Atlantic coast and more Mediterranean-type climate further east. Holocene pollen records from the Peninsula suggest that this gradient was less steep during the mid-Holocene, possibly reflecting the impact of orbital changes on circulation and thus regional patterns in climate. Here, we use 7214 pollen samples from 117 sites covering part or all of the la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 163 publications
0
6
0
Order By: Relevance
“…Differences in the trend of moisture availability between the models imply that the nature of the changes in circulation varies between models and thus the simulations do not provide a strong basis for explaining the observed patterns of change in moisture availability. Earlier studies, focusing on the western Mediterranean (Liu et al, 2023), Europe (Mauri et al, 2014), and central Eurasia (Bartlein et al, 2017), have shown that models have difficulty in simulating the enhanced moisture transport into the Eurasian continent shown by palaeoenvironmental data during the mid Holocene and during the late Holocene. Changes in precipitation can also affect landsurface feedbacks.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Differences in the trend of moisture availability between the models imply that the nature of the changes in circulation varies between models and thus the simulations do not provide a strong basis for explaining the observed patterns of change in moisture availability. Earlier studies, focusing on the western Mediterranean (Liu et al, 2023), Europe (Mauri et al, 2014), and central Eurasia (Bartlein et al, 2017), have shown that models have difficulty in simulating the enhanced moisture transport into the Eurasian continent shown by palaeoenvironmental data during the mid Holocene and during the late Holocene. Changes in precipitation can also affect landsurface feedbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in precipitation can also affect landsurface feedbacks. Liu et al (2023), for example, have argued that enhanced moisture transport into the Iberian peninsula during the mid Holocene led to more vegetation cover and increased evapotranspiration and had a significant impact on the reduction of growing season temperatures. Differences in the reconstructed trends of summer temperature and plantavailable moisture through the Holocene suggests that this land-surface feedback was not an important factor influencing summer temperatures in the EMBSeCBIO region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations